2013
DOI: 10.5505/sakaryamj.2013.54872
|View full text |Cite
|
Sign up to set email alerts
|

Testicular tumors in children

Abstract: ÖzetÇocuklarda testis tümörleri nadirdir. Teratomlar ve yolk sac tümörleri çocuklarda en sık görülen testis tümörleridir. Testis tümörleri sıklıkla ağrısızdır. Bu yanlışlıkla hidrosel tanısına neden olur. Tanıda tümör belirteçleri ve ultrasonografi kullanılmaktadır. Benign tümörler malign tümörlerden daha sık görülmektedir. Testis tümörlerin temel tedavisi inguinal orşiyektomidir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…8 It has been shown that 75% of tumors of the scrotum, including malignant tumors, occur before the second year of life of a child, which correlates with period of occurrence of FHI. 7 Our patient had unspecific clinical presentation and medical history. Guided by this information, during preoperative follow-up period, working diagnosis was hydrocele funiculi.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…8 It has been shown that 75% of tumors of the scrotum, including malignant tumors, occur before the second year of life of a child, which correlates with period of occurrence of FHI. 7 Our patient had unspecific clinical presentation and medical history. Guided by this information, during preoperative follow-up period, working diagnosis was hydrocele funiculi.…”
Section: Discussionmentioning
confidence: 79%
“…This case demonstrates a rare tumor of the scrotal region which, due to its nonspecific clinical picture, presents a diagnostic and therapeutic challenge in clinical practice. Considering the nonspecific clinical picture, the consistency of the formation, the area it affects, and its tendency to grow, in terms of differential diagnosis, several conditions can be taken into account 7 8 9 10 ( Table 1 ). Out of all diseases, malignant ones deserve special attention.…”
Section: Discussionmentioning
confidence: 99%
“…Testisin yeri ile malignensi arasında doğru orantı mevcuttur. İntraabdominal testislerde malignensi gelişme ihtimali inguinal testislere oranla daha yüksektir 20 . İnmemiş testisli hastalarda testis torsiyonu ve travma ihtimali normale göre artmış olarak tespit lerek testis skrotuma indirilmesi sağlanır 7,8 .…”
Section: Cerrahi Tedavi;unclassified